How to fabricate the structure
The dense aggregate structure addresses residual stresses and poor crystallinity in oxide ceramics by forming a cohesive film with low porosity and high crystallinity, enhancing piezoelectric and dielectric performance and enabling flexible, high-density films for wearable devices and solid lithium-ion batteries.
Patent Information
- Application Number
- JP2023105124
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-29
- Filing Date
- 2023-06-27
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2040-05-27
AI Technical Summary
Conventional methods for producing oxide ceramics face challenges such as residual stresses, poor crystallinity, and limited density due to differences in linear expansion coefficients, leading to deterioration in piezoelectric and dielectric performance, and issues with internal stress changes in solid lithium-ion secondary batteries, as well as limitations in forming high-density films without gaps or cracks.
A method involving the use of a highly dense aggregate structure formed by pressing fine particles of brittle material onto a transfer plate, followed by repeated lamination and impregnation with a liquid resin, resulting in a cohesive film with a porosity of 20% or less and a mesh-like structure that maintains high crystallinity and reduces internal stress.
The method achieves a highly dense aggregate with improved piezoelectric and dielectric properties, enhanced ion conductivity, and the ability to form flexible, crack-free films suitable for wearable devices and all-solid lithium-ion batteries operating at room temperature.
Smart Images

Figure 0007628329000002 
Figure 0007628329000003 
Figure 0007628329000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a new structure of oxide ceramics. Oxide ceramics are widely used as electronic ceramics that utilize their piezoelectricity, dielectricity, etc. Recently, there has been a demand for the development of "flexible devices" that combine electronic ceramics with flexible organic materials such as plastics in order to adapt them to wearable devices. In addition, the "oxide all-solid-state lithium-ion secondary battery," which has been attracting attention as the next-generation storage battery, requires highly advanced technology, such as preparing the positive electrode mixture and the negative electrode mixture by depositing the oxide ceramic active material, solid electrolyte, and auxiliary agent for enhancing conductivity evenly on a metal foil without any gaps, and then bonding these positive electrode mixture and negative electrode mixture with the oxide solid electrolyte without any gaps. [Background technology]
[0002] Oxide ceramics generally require extremely high firing temperatures to sinter into a highly dense material, but the plastics and inexpensive, flexible metal foils such as aluminum and copper used in flexible devices and oxide all-solid-state lithium-ion secondary batteries have an extremely low heat resistance and cannot withstand the sintering temperatures and oxidizing atmosphere of oxide ceramics. Conventionally, methods for producing oxide ceramic structures have included adding additives to lower the sintering temperature or to impart reduction resistance; applying techniques such as sputtering, PLD, CVD, MOD (sol-gel), hydrothermal synthesis, screen printing, EPD, and cold sintering to deposit oxide ceramic films at temperatures lower than the sintering temperature; shaping raw material particles into nano-sized sheets or cubes and laminating them; and aerosol deposition (AD) methods in which raw material particles are solidified by colliding them with a substrate at room temperature. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-100069 A [Patent Document 2] JP 2006-043993 A [Patent Document 3] JP 2012-240884 A [Patent Document 4] JP 2012-188335 A [Patent Document 5] Patent Application No. 2018-110527 [Non-patent literature]
[0004] [Non-Patent Document 1] Yoshio Uchida et al., Sumitomo Chemical 2000-I, p.45 Summary of the Invention [Problem to be solved by the invention]
[0005] It is well known that oxide ceramics generally have a high Young's modulus and very high hardness, and are therefore susceptible to the effects of residual stress acting within. However, in conventional manufacturing methods involving heat treatment, such as the sputtering method, PLD method, CVD method, MOD method (sol-gel method), hydrothermal synthesis method, screen printing method, EPD method, and cold sintering method, it is known that even when deposition is performed at a temperature lower than the sintering temperature, residual stress occurs in the oxide ceramic film due to a slight difference in the linear expansion coefficient between the substrate and the oxide ceramic film, leading to deterioration of piezoelectric and dielectric performance. In addition, even in ceramic films deposited at room temperature by methods such as AD, the internal compressive stress caused by the shot peening effect becomes a residual stress, which leads to deterioration of the dielectric properties. In all-solid-state oxide lithium-ion secondary batteries, the insertion and removal of lithium ions into and from the active material causes expansion and contraction, which in turn causes changes in internal stress, which can lead to cracks in the active material itself and thus to performance degradation.
[0006] The polarization mechanism of ferroelectrics, which exhibit large piezoelectricity, is due to the domain walls formed due to the anisotropy of the crystal, which move when a high electric field is applied, achieving polarization inversion and polarization rotation. However, if there are areas where a clean interface is not formed, areas with imperfect crystallinity (areas where the lattice image observed by TEM is unclear), or areas containing oxygen defects, the movement of the domain walls is pinned or clamped, preventing sufficient polarization inversion and polarization rotation, which is known to result in deterioration of the ferroelectricity and piezoelectricity. Therefore, it is necessary to synthesize oxides with high crystallinity and few defects. Similarly, in oxide solid electrolytes, lithium ions mainly move along the conductive paths formed within the crystals; therefore, if there are any areas with incomplete crystallinity or if there is a binder between particles that does not exhibit the ionic conductivity of lithium ions, this will lead to a decrease in ionic conductivity, so it is necessary to obtain high-quality crystals. However, when low-temperature deposition is performed using conventional techniques such as sputtering, PLD, CVD, MOD (sol-gel), hydrothermal synthesis, screen printing, EPD, and cold sintering, which promote crystal growth to obtain highly dense films, it is extremely difficult to obtain high crystallinity, and there are also problems such as the fact that the substrates that can be used are quite limited. In addition, while the AD method can deposit films using high-quality fine particles of oxide ceramic raw materials, the miniaturization of the raw material particles, which is unique to the AD method, results in size effects that reduce the piezoelectricity and dielectric properties, and in oxide solid electrolytes, there are problems such as the formation of many grain boundaries that act as barriers to the movement of lithium ions, reducing ionic conductivity. Furthermore, in methods for depositing ceramic films in aqueous solutions, such as hydrothermal synthesis and EPD, hydroxyl groups and other residues remain at the grain boundaries, which are known to be a problem in that they can increase the leakage current of ferroelectrics and inhibit lithium ion conduction.
[0007] Conventional ceramic deposition techniques, such as sputtering, PLD, CVD, MOD (sol-gel), hydrothermal synthesis, screen printing, and EPD, are techniques for depositing oxide ceramic films on a substrate. However, in oxide all-solid-state lithium-ion secondary batteries and the like, it is necessary to form a highly dense ceramic film between the aluminum or copper foil current collectors, and a new deposition method that enables bonding different from conventional ceramic deposition techniques is required. In the AD method, deposited sulfide solid electrolytes are placed opposite each other and then pressurized, thereby realizing bonding associated with high density of the sulfide solid electrolyte layer (Patent Document 1). However, when this method is applied to oxide solid electrolytes in which lithium ions move within the crystals, many grain boundaries that act as barriers to the movement of lithium ions are formed as the particles are miniaturized, so that bonding without crushing the raw material fine particles is an issue.
[0008] In addition, there is a demand for a method that allows highly dense deposition at atmospheric pressure rather than using vacuum or reduced pressure processes such as sputtering, PLD, CVD, and AD.
[0009] Unlike conventional deposition methods involving crystal growth through heat treatment, such as sputtering, PLD, CVD, MOD (sol-gel), hydrothermal synthesis, screen printing, and EPD, the pressure molding method, in which raw material particles are packed into a mold and pressure molded to obtain a structure, has a challenge, as shown in Non-Patent Document 1, of achieving a relative density of 80% or more (void ratio of 20% or less) of the structure without crushing the raw material particles. In general, any oxide ceramic particles always have a "cohesive bonding force", and it is known that as the particles become smaller and the specific surface area becomes larger, the bonding force becomes stronger, making them more likely to aggregate. In conventional pressure molding methods, this cohesive bonding force occurs before the particles completely fill the voids, and strong friction caused by the molding pressure is also added to this, making it impossible to manufacture highly dense structures. In order to manufacture structures with a relative density of 80% or more (void ratio of 20% or less) by pressure molding, a method involving pulverization of the raw material particles has been used, similar to the AD method (Patent Document 2). In addition, the cold sintering method is a technique for producing highly dense oxide ceramics by forming an amorphous layer around raw material particles and then applying pressure. However, with non-thermal treatment, an amorphous layer remains around the raw material particles, which reduces the piezoelectricity, dielectric property, ionic conductivity, etc., and ultimately requires heat treatment to grow the amorphous layer into high-quality crystals. Another problem is that there is a limit to the raw material particles that can form an amorphous layer. Nanosheets made by thinly exfoliating oxides (Patent Document 3) can deposit highly dense oxide layers without heat treatment, but because oxide sheets several nm thick are deposited one layer at a time, there is a problem with depositing them to thicknesses of submicrons. Similarly, a technology for regularly arranging cubic nanoparticles in three dimensions has been attracting attention recently (Patent Document 4), but in reality, even slight differences in size of the cubic raw material particles can cause widespread cracks, making it difficult to form a uniform film without gaps on the substrate.
[0010] Compacts with a porosity of more than 20% and compacts in which fine particles are bound with a binder by filling 20% or more of the voids with resin also have the problem of not being able to obtain functionality due to the crystal structure. For example, in the case of piezoelectrics and ferroelectrics, the oxides with functionality have a relative dielectric constant 50 to 1000 times higher than that of the resin, so that electric field concentration occurs in the resin with a low relative dielectric constant, resulting in problems such as insufficient electric field being applied to the oxide, increased leakage current, and reduced dielectric breakdown strength. Even in oxide-based all-solid-state lithium-ion batteries, even if a polymer electrolyte can be mixed or impregnated to fill the voids in the oxide solid electrolyte, the polymer electrolyte has a Li-ion conductivity 50 to 1000 times lower than the oxide solid electrolyte, and the rate is limited by the ionic conductivity of the polymer electrolyte, and the diffusion of Li ions necessary for charging and discharging does not occur. [Means for solving the problem]
[0011] The present inventors have intensively studied structures that can solve the above-mentioned problems of the prior art, and as a result, have found that a structure in which the fine particles are densely arranged and have a porosity of 20% or less can be fabricated by repeatedly transferring a thin layer of fine particles of a brittle material such as PZT provided on a transfer plate to a substrate at a pressure lower than the pressure at which the fine particles are crushed, and have previously filed a patent application (Patent Document 5, unpublished at the time of filing the present application). The present inventors further found that the structure has fine, mesh-like nanovoids that extend throughout the structure between the densely arranged fine particles, and that the structure can solve the above-mentioned problems. The nanovoids may be impregnated with a liquid organic material such as resin or silicone oil, and the liquid resin may be solidified after impregnating the high-density aggregate. Specifically, the gaps that still exist between the densely packed first particles having a large particle size are filled by second particles that are smaller than the first particles, thereby creating an extremely dense agglomerate structure with a void ratio of 20% or less. The high-density agglomerate according to the present invention maintains the functionality due to the crystal structure because the above-mentioned production method hardly causes crushing of the raw material particles, and has a network structure in which most of the voids are connected by minimizing crystal growth and crushing of the raw material particles. The high-density agglomerate according to the present invention can be seen as a structure in which the spaces present in a powder in which the first and second particles are mixed are reduced to the point where the interparticle distance is in the nanometer range, and therefore has the characteristic that the specific surface area of the powder and the specific surface area of the high-density agglomerate according to the present invention are almost the same.
[0012] The void structure of this highly dense agglomerate is preferably characterized by nanovoids formed by the second particles in the voids between the first particles, as shown in FIG. 1(a). In contrast, in typical sintered bodies that undergo heat treatment, nano-voids disappear due to crystal growth, and densification, which involves crushing of raw material particles, also eliminates nano-level voids. As a result, a structure is formed in which voids containing grain boundary triple junctions are scattered, as shown in Figure 1(b).
[0013] The following is an example of making a highly dense agglomerate. As the transfer plate, a metal plate having a high elastic modulus so that no brittle material remains during pressure transfer is used, and when particles made of a brittle material are attached to the transfer plate, first particles having a large particle size are attached first, and then second particles having a particle size smaller than the first particles are attached thereon. A base material made of a metal or carbon having a low elastic modulus enough for the brittle material to adhere during pressure transfer is placed on the side on which the second particles are attached, and pressure is applied lower than that at which these particles are crushed, thereby transferring the thin layer of brittle material attached to the transfer plate onto the base material. Subsequently, by a similar method, the first particles and the second particles are attached on the transfer plate, and the thin layer side of the brittle material of the substrate to which the thin layer of brittle material has been transferred is placed on the side on which the second particles are attached, and pressure is applied to transfer the thin layer of brittle material attached to the transfer plate onto the thin layer on the base material. By repeating the lamination process, a brittle material structure having a desired thickness is produced on the base material. In forming the thin layer of brittle material on the transfer plate, first particles having a large particle size may be deposited first, then a mixture of the first particles and second particles having a smaller particle size than the first particles may be deposited thereon, and then the second particles may be deposited thereon. When the thin layer of the brittle material attached to the transfer plate is transferred to the substrate under pressure, vibration may be applied in the lateral direction.
[0014] Specifically, the present application provides the following inventions: <1> A highly dense agglomerate of brittle material particles, characterized in that the highly dense agglomerate has interfaces between the brittle material particles where the particles are bonded to each other and voids where the particles are not bonded, a porosity, which is the volume ratio of the voids to the entire highly dense agglomerate, is 20% or less, and the ratio of the volume of voids connected to the apparent outer surface of the highly dense agglomerate to the total void volume of the highly dense agglomerate is 65% or more. <2> The highly dense agglomerate described in <1>, characterized in that the brittle material microparticles constituting the highly dense agglomerate consist of a first brittle microparticle and a second brittle microparticle smaller than the first brittle microparticle, the second particle is located in the gap between the first particles which are bonded to each other, and there are further gaps between the bonding interfaces between the particles and between multiple second particles in the gap, and between the second particle and the surrounding first particles, and there are also gaps that are not bonded. <3> The second particle particle size The highly dense aggregate according to <2>, characterized in that the size is 1 μm or less. <4> The highly dense agglomerate according to <1>, characterized in that an average void width between the brittle material fine particles is 200 nm or less. <5> The highly dense aggregate described in any one of <1> to <4>, wherein the voids in the highly dense aggregate are impregnated with silicone oil, a liquid in which nanoparticles having a particle size of 100 nm or less are dispersed, or a liquid resin. <6> The highly dense agglomerate according to <5>, wherein the liquid resin impregnated into the highly dense agglomerate is solidified. <7> An electric element unit, comprising a film made of the dense aggregate described in any one of <1> to <4>, an electrode layer, and an electrically conductive mesh-like foil sequentially laminated on both sides of a substrate, the dense aggregate being impregnated with a resin. <8> An electric element unit comprising a plurality of units according to <7> stacked together. <9> A solid-state battery comprising a first polymer impregnated in the dense agglomerate according to any one of <1> to <4>, wherein the first polymer has ion conductivity. <10> The first polymer, a second polymer formed on the first polymer, The second polymer has ion conductivity, The solid-state battery according to <9>, wherein the second polymer contains brittle material particles. <11> The solid-state battery according to <10>, wherein the solid-state battery has a folded shape. <12> The solid-state battery according to <10> or <11>, wherein the solid-state battery is folded and stacked. Effect of the Invention
[0015] According to the present invention, a powder of raw material fine particles of a brittle material having high crystallinity is pressed at a pressure lower than the pressure at which the particles are crushed to form a thin pressure-molded structure in which the raw material fine particles are arranged in a highly dense manner, and then a structure in which the raw material fine particles are similarly arranged in a highly dense manner is stacked on top of the above structure by pressure molding so as to be integrated with the structure, thereby obtaining a highly dense agglomerate formed by agglomeration of the raw material fine particles and having a relative density of 80% or more (void ratio of 20% or less).
[0016] In addition, the fine second particles have high liquid / solid interfacial free energy due to contact with liquid, and the contact angle of the liquid is low, thereby exhibiting excellent wettability. Most of the voids in the high-density aggregate of the present invention are made of the fine second particles, and the void width is extremely narrow at 200 nm or less, so the high-density aggregate of the present invention is characterized by a very strong capillary phenomenon. That is, while conventional ceramics have high barrier properties against gases and liquids as they become more dense, the high-density aggregate film of the present invention is characterized by having very high impregnation properties without exhibiting barrier properties against liquids and gases even when densification is promoted. Therefore, the high-density aggregate of the present invention can be impregnated into every corner of the structure even with a highly viscous liquid or a liquid with high surface tension.
[0017] Since the brittle material structure of the present invention is formed by agglomeration of raw material fine particles, it is possible to maintain the high crystallinity of the original raw material fine particles, and the generation of internal stress is reduced.
[0018] According to the present invention, there is no need for sintering, crushing of raw material fine particles, processes under vacuum or reduced pressure, etc., which have conventionally been required to produce a high-density oxide ceramic structure, and the generation of defects and internal stress within the crystals that are associated with these processes can be suppressed.
[0019] According to the present invention, even when the highly dense aggregate is sintered, there is an effect of suppressing deposition shrinkage as compared with the conventional ceramic method involving heat treatment.
[0020] According to the present invention, by impregnating a high density aggregate of a piezoelectric or ferroelectric with silicone oil, resin, or nanoparticles, it becomes possible to control the electric field strength applied to the brittle material particles of the piezoelectric or ferroelectric. Specifically, by impregnating with a material having a lower dielectric constant than the brittle material fine particles of the piezoelectric or ferroelectric, it becomes possible to increase the coercive field and improve the dielectric breakdown strength. In addition, by impregnating with nanoparticles having a higher dielectric constant than the brittle material fine particles of the piezoelectric or ferroelectric, it becomes possible to increase the electric field strength applied to the brittle material fine particles of the piezoelectric or ferroelectric, thereby decreasing the coercive field and improving the piezoelectricity. In addition, by impregnating a high density aggregate of an oxide solid electrolyte with a polymer solid electrolyte, it becomes possible to improve the density of the oxide solid electrolyte in which lithium ions can move at high speed, shorten the movement distance of the lithium ions in the polymer solid electrolyte, and increase the diffusivity of the lithium ions. [Brief description of the drawings]
[0021] [Figure 1] FIG. 2 is a schematic diagram showing the difference in void structure between the highly dense agglomerate of the present invention and a conventional high-density ceramic sintered body. [Diagram 2] 3D SEM image of a highly dense aggregated film of PZT according to the present invention. [Diagram 3] 3D SEM image of a representative PZT sintered body. [Figure 4] FIG. 1 is a diagram showing the difference between ceramics that can be produced by conventional ceramic methods and ceramics that can be produced using highly dense aggregates in terms of the relationship between porosity and the volume density of pores communicating with the outer surface relative to the total pores. [Diagram 5] SEM images of fracture surfaces of films in which a dense PZT film is impregnated with epoxy resin or PMMA resin. [Figure 6] A comparison of the leakage current characteristics of a PZT powder film and a highly dense PZT coagulated film. [Figure 7] A comparison diagram of the polarization characteristics of a PZT highly dense coagulated film encapsulating silicone oil and a PZT highly dense coagulated film encapsulating TiO2 nanoparticles. [Figure 8]A schematic diagram of element unit 1 in which a PZT highly dense agglomerated film impregnated with PMMA, an electrode layer, and an electrically conductive mesh-like foil are laminated on both sides of a substrate, a photograph showing the appearance of unit 1, and a schematic diagram of element unit 2 in which multiple units 1 are laminated. [Figure 9] A photograph showing the appearance of a PZT highly dense coagulated film fabricated using an electrically conductive mesh foil as a substrate. [Figure 10] This photograph shows how an integrated element unit cannot be obtained when electrically conductive mesh foil is laminated directly onto the dense PZT coagulation films provided on both sides of the substrate without impregnating PMMA and without an electrode layer in between. [Figure 11] This is a schematic diagram showing the manufacturing procedure for exposing the electrode layer on the surface of a PZT high-density agglomerate film that has been impregnated with and cross-linked with epoxy resin, by swelling and peeling off only the epoxy resin on the surface of the PZT high-density agglomerate film. [Figure 12] SEM images comparing the surface of a highly dense cohesive PZT film that has had its surface epoxy resin peeled off by swelling it, and the surface of a highly dense cohesive PZT film that has an epoxy resin surface. [Figure 13] A comparison diagram of the polarization characteristics of a highly dense cohesive PZT film in which the epoxy resin on the surface has been swelled and peeled off, and a highly dense cohesive PZT film with an epoxy resin on the surface. [Figure 14] SEM images of the first and second LCO particles. [Figure 15] SEM images of the first and second LTO particles. [Figure 16] A schematic diagram showing the manufacturing procedure for a solid-state battery in which positive and negative electrode sheets are impregnated with a polymer electrolyte and then bonded together with the polymer electrolyte on the surface of each sheet, and then cross-linked; and a schematic diagram of a solid-state battery with a sheet of polymer solid electrolyte between the positive and negative electrode sheets. [Figure 17] This graph compares the charge / discharge characteristics of a solid-state battery in which the positive and negative electrode sheets are impregnated with a polymer electrolyte and then bonded together with the polymer electrolyte on the surface of each sheet, and a solid-state battery in which a sheet of polymer solid electrolyte is placed between the positive and negative electrode sheets. [Figure 18]Schematic diagram of a solid-state battery manufactured by folding a battery sheet and a solid-state battery manufactured by stacking folded battery sheets. [Figure 19] A schematic diagram of a solid-state battery with a polymer electrolyte layer in which brittle material particles are embedded, a photograph of a folded solid-state battery, and a photograph of a folded and stacked solid-state battery with an LED turned on. [Figure 20] Charge and discharge characteristics of a broken solid-state battery. [Figure 21] Comparison of impedance characteristics before and after folding the polymer solid electrolyte between the aluminum foils EXAMPLES
[0022] Example 1: Pore structure of highly dense cohesive film using PZT particles Next, a specific method for producing the structure of the present invention will be described. The first particles, PZT particles (average particle size : 1550 nm) was attached. The first PZT particles were synthesized by the molten salt method using PZT-LQ powder manufactured by Sakai Chemical Industry Co., Ltd. The first PZT particles were weighed with a micro-analytical balance (SHIMADZU, MODEL: AEM-5200) and transferred to a 50cc glass container containing ethanol, and dispersed for 1 minute with ultrasonic waves of 350W and 20kHz using an ultrasonic homogenizer (SONIC & MATERIALS, MODEL: VCX750). The solution was transferred to an airbrush coating system (GSI Creos, PS311 airbrush set) and spray-painted onto a SUS304 transfer plate prepared in advance on a hot plate set at 60℃, thereby attaching the first PZT particles to the SUS304 surface.
[0023] Next, the second particles were attached onto the first particles so that the mixing ratio of the second particles (volume occupied by the second particles / combined volume of the first particles and the second particles) was between 15% and 30%. The second particles are sprayed in the same manner as the first particles. The second particles are PZT particles (average particle size The second PZT particles were obtained by first preparing a sintered body using Sakai Chemical Industry's PZT-LQ powder, powdering it in a mortar, placing it in a zirconia ball mill pot together with zirconia balls and acetone, pulverizing it in a planetary ball mill, drying the acetone, dispersing the resulting powder in ethanol, centrifuging it, and classifying it. The second PZT particles were also dispersed in ethanol in the same way as the first PZT, and then sprayed onto the surface of the SUS304 to which the PZT particles were attached, causing them to adhere onto the first PZT particles.
[0024] The SUS304 with the first and second particles attached was removed from the hot plate and 2 A number of disks of φ were cut out, and the first and second particles were pressed against an aluminum foil (film thickness 20 μm) substrate, pressed, transferred, and solidified onto the substrate. The substrate is preferably a metal or carbon with an elastic modulus of 180 GPa or less. The solidification pressure is preferably lower than the pressure at which the raw material fine particles are crushed, and is preferably 2 GPa or less. In this experiment, pressure was applied at two levels: 1000 MPa and 400 MPa. The first and second particles were pressed and transferred from the SUS304 to the aluminum foil substrate nine times, resulting in a highly dense PZT coagulated film (pressurized at 1000 MPa) and a compressed powder film (pressurized at 400 MPa) laminated on the aluminum foil.
[0025] As a comparative reference example, PZT-LQ powder manufactured by Sakai Chemical Industry Co., Ltd. was sintered to obtain a sintered body having a relative density of about 80%.
[0026] The specific surface areas of the obtained high density cohesive film, pressed powder film, and low density sintered body were evaluated by the multipoint BET method (Kr gas adsorption method). The results are summarized in Table 1. The true density of PZT is 8.0 g / cm 3 The specific surface area of the powder was the average of the first and second PZT particles. particle sizeThe specific surface area of the powder was calculated from the particle size assuming that the PZT particles exist as powder. In both cases, it is assumed that the PZT particles themselves are non-porous. The weights of the PZT layers of the high-density aggregate film and the pressed powder film were calculated by measuring the weights before and after depositing the first and second PZT particles on the aluminum foil, and taking the difference between the weights. The film thicknesses of the high-density aggregate film and the pressed powder film were obtained by observing cross-sectional SEM images and calculating the average film thickness. From these results, the density of the PZT layers of the high-density aggregate film and the pressed powder film was calculated, and this was divided by the true density of PZT to calculate the relative density (%) of the PZT layer, and then subtracted from 100 to calculate the overall porosity (%) of the PZT layer. The specific surface area of the PZT layer was evaluated by the BET method while the PZT film was still deposited on the aluminum foil. Because the specific surface area of the aluminum foil is negligibly small compared to the specific surface area of the PZT layer, the specific surface area per weight of the entire PZT film including the aluminum foil obtained by the BET method was converted into the value per weight of the PZT layer contained in the PZT film, and the specific surface area of just the PZT layer was calculated from the weight of the deposited PZT film. The surface area measured by the BET method is the surface area that the measurement gas, Kr, can reach from the apparent outer surface of the measurement sample, so the specific surface area of the PZT layer measured by the BET method corresponds to the value obtained by subtracting the specific surface area of the interface that is generated when powder particles are bonded to each other when the PZT layer is formed from the powder, and the specific surface area corresponding to the void portion that becomes the closed space inside the PZT layer as a result of this, from the specific surface area of the powder. Here, the shapes of the pores in the high-density agglomerated film, the pressed powder film, and the low-density sintered body are all uniform overall, so the ratio of the specific surface area of the PZT layer measured by the BET method to the specific surface area in powder form can be approximated to the proportion of the pores that are connected to the apparent outer surface of the PZT layer among all the pores in the PZT layer. [Table 1]
[0027] The PZT film obtained by pressing at 400 MPa had a porosity of 33.5%, which was equivalent to that of a normal green compact, while the PZT film obtained by pressing at 1000 MPa had a porosity of 10%, which was highly dense. The specific surface area of the PZT layer in both the PZT green compact and the PZT highly dense coagulated film was 1.29 m 2 / g, and the volume density of the voids communicating with the apparent outer surface relative to the total voids was also 98% or more. Furthermore, a comparison of the specific surface area of the powder in Table 1(6) with the specific surface area of the PZT layer in Table 1(16) indicates that the contact area between PZT fine particles in the PZT highly dense agglomerated film and the area of the part of the fine particles facing the voids trapped inside by the junctions between the fine particles are only about 2% of the total specific surface area of the fine particles, and the highly dense PZT agglomerated film of the present invention has the characteristic that the specific surface area is almost the same as that of the powder, even when the void ratio is highly densified to 10%. The sintered body of the comparative example has a porosity of 21.8% and a specific surface area of 0.43 m 2 / g, and the volume density of voids communicating with the apparent outer surface was 42.8% of the total voids. Thus, the highly dense PZT agglomerated film of the present invention has a porosity of 20% or less, a high density film that could not be achieved in the past without sintering or crushing the particles, and has the extremely unique feature of being able to maintain a large specific surface area after agglomeration that is comparable to the specific surface area of the fine particles before agglomeration. Next, the detailed microstructures of the PZT dense coagulated film and the PZT sintered body were examined by three-dimensional SEM observation. The PZT dense cohesive film was prepared in the same manner as the sample used in the BET evaluation. The pressing pressure was 750 MPa, and the porosity of the cohesive film was 14%. As a comparative reference sample, a sintered body with a porosity of 4% was prepared. To obtain a 3D SEM image, a planar image of the surface is first obtained, the surface observed with FIB is then thinly scraped off (50 nm thick for highly dense cohesive films, 100 nm thick for sintered bodies), and a planar image is obtained again. The huge amount of image data obtained is then digitally processed to reproduce it as 3D CG, allowing numerical analysis of the microstructure, etc. The experimental conditions and results are summarized in Table 2. FIG. 2(a) shows a cross-sectional SEM image of the PZT dense aggregated film used in the 3D SEM observation. In the 3D SEM observation, the area enclosed by a square (7 μm × 7 μm) in the cross-sectional image was observed to a depth of 7 μm. FIG. 2(b) shows a 3D image reproducing the microstructure of the PZT dense aggregated film, (c) shows the void structure of the entire observed area, (d) shows the void portion with the largest volume among the entire voids, which is connected to each other and also to the outer surface of the observed area, and (e) shows the void portion closed and isolated inside the observed area other than the voids connected to the outer surface. FIG. 3(a) shows a 3D SEM image reproducing the microstructure of the sintered body, and (b) shows a 3D image of the void structure of the entire observed area. The black parts in Figure 3(b) are voids that are connected to the outer surface of the observed area, and the gray parts are voids that are isolated inside.
[0028] From Fig. 2(a), it can be seen that the PZT dense aggregate film deposited at 750 MPa is uniform and has high density. From Fig. 2(c) and (d), it can be seen that the void structure of the PZT dense aggregate is a mesh-like structure that spreads throughout the observed area. but It can be seen that most of the voids are integrated, and from Fig. 2(e) it can be seen that there are few isolated voids inside. On the other hand, it can be seen that the void structure of the sintered body in Fig. 3(b) is scattered within the bulk starting from the grain boundary triple junctions, and there is little interconnection between the voids. The results of the microstructural observations using 3D SEM are not inconsistent with the microstructures of the PZT dense agglomerates and PZT sintered compacts derived from the BET specific surface area determined using the multi-point BET method described above, supporting the validity of the above considerations made using the BET specific surface area. In addition, the specific surface area of the voids that communicate with the outer surface of the PZT highly dense cohesive film created at a press pressure of 750 MPa, which was used in the above 3D SEM analysis, is approximately 1 / 100th of that of the raw material particles. particle size The specific surface area of the raw material particles calculated from the size and mixture ratio (73.8:26.2), and the volume density (98%) of the voids communicating with the outer surface relative to the total voids, as analyzed from a 3D SEM image, were 11.23 μm 2 / μm 3It can be estimated that:
[0029] Figure 4 shows the relationship between the volume density of the pores that are connected to the outer surface and the overall porosity, derived from the results of the multi-point BET method and 3D SEM image observation described above. The three white circles on the upper solid line in Figure 4 are plots of PZT aggregates obtained using the aggregate manufacturing method used in the present invention, with consolidation pressures of 400 MPa, 750 MPa, and 1000 MPa, respectively, from the right. Of these, the two on the left have a porosity of 20% or less and correspond to the highly dense aggregates of the present invention, while the one on the right is a green compact with a porosity of 33.5%, outside the range of the present invention. In all of these, the specific surface area of the voids communicating with the outer surface is nearly equal to the specific surface area of the raw material powder. The lower solid line in FIG. 4 shows the relationship between the volume density of the voids communicating with the outer surface of the PZT sintered body and the overall porosity. The right black circle is a plot of the molded body (uncompressed) before sintering, the middle black circle is a plot of the sintered body obtained in this example with a porosity of 21.8%, and the left black circle is a plot of the same sintered body with a porosity of 4%. Thus, in a sintered body, as the raw material particles undergo crystal growth during sintering, the porosity decreases, and the volume density of pores communicating with the outer surface relative to the total pores also decreases. In Figure 4, the dotted line in the center shows the relationship between the volume density of voids connected to the outer surface and the overall porosity of a compact obtained from a powder compact of alumina particles obtained by a conventional one-stage compression, within the range in which crushing of the raw material particles is minimized, regardless of the agglomerate manufacturing method of the present invention. The black squares on the dotted line are plotted for the aluminas described in Patent Document 5 and Non-Patent Document 1 as compacts having the minimum porosity known in the art, which can be obtained by a normal one-stage compression within a range in which crushing of the raw material particles is suppressed as much as possible. Considering that the alumina in question is a compact, the volume density of the pores communicating with the outer surface relative to the total pores is assumed to be the same value as that of the compact in the upper part of Figure 4, and is plotted on the solid line in the upper part of Figure 4. It is believed that it is possible to further reduce the porosity by, for example, sintering the molded body or by molding involving crushing the raw material particles. However, it is believed that as a result of this, the volume density of the voids communicating with the outer surface relative to the total voids will also decrease, as shown by the dotted line, due to crystal growth or crushing of the raw material particles. The above plots for PZT sintered body and alumina show that in conventional ceramic processes involving heat treatment and particle crushing, as the porosity decreases, the voids that were integrated in the green compact become scattered, resulting in a tendency for the maximum void density to decrease. On the other hand, since the highly dense agglomerate of the present invention minimizes crushing of the raw material particles and does not undergo crystal growth, even if the porosity is 20% or less, it can maintain a volume density relative to the total voids, which is nearly 100% of the voids connected to the outer surface, the same as that of a typical pellet compact before sintering. The above plot for alumina and the curve for the sintered PZT body show the limit ranges for the porosity and volume density of voids communicating with the outer surface relative to the total voids in the prior art, while it is clear that the high density agglomerate according to the present invention, by further sintering or compressing it for example, can be used to produce a structure having a porosity of 20% or less and a volume density of voids communicating with the outer surface relative to the total voids of 60-65% or more.
[0030] The average gap width between the fine particles of the dense aggregate of the present invention is preferably 200 nm or less from the viewpoint of impregnation with silicone oil, a liquid in which nanoparticles are dispersed, or a liquid resin, which will be described later. The specific surface area of the gap portion communicating with the outer surface of the PZT dense aggregate film observed in the three-dimensional SEM image shown in Figure 4 is 11.23 μm as described above. 2 / μm 3 The average void width of the voids that communicate with the outer surfaces of the PZT particles in the PZT dense agglomerated film can be estimated as the void volume (48.38 μm 3 ) to "Half of the surface area (11.23 μm 2 / μm 3 ×343 μm 3 When approximated by dividing it by "narrow gap / 2", it comes to 25 nm.
[0031] Figure 5(a) is an SEM image of the fracture surface of a PZT dense coagulation film that was impregnated with epoxy and solidified. The PZT dense coagulation film deposited on aluminum foil was punched out into circles with diameters of 11.24 mm and 13 mm, and a drop of low-viscosity epoxy resin (2-part type, 50-minute curing, manufactured by Shin-Nihon Resin Co., Ltd.) was dropped onto the surface of the PZT film. The two PZT dense coagulation films were then placed facing each other and cured under a pressure of 400 MPa. Figure 5(b) is an SEM image of the fracture surface of a film obtained by impregnating and solidifying a highly dense cohesive PZT film with PMMA. PMMA was dissolved in acetone and sprayed onto the first and second PZT particles on the SUS foil, then dried and turned back into powder. The amount of PMMA sprayed was equal to the volume of voids that were generated when the first and second PZT particles were densified. The first and second PZT particles on the SUS foil and the PMMA powder were repeatedly pressed onto aluminum foil to form a highly dense cohesive film, after which acetone was dropped with a dropper to re-dissolve the PMMA, which was then dried and re-solidified to produce the film.
[0032] <Example 2> Properties of highly dense cohesive films using PZT particles Next, the leakage current characteristics and polarization characteristics of the dense aggregate film according to the present invention were examined. To evaluate the electrical properties, Au electrodes with an area of 0.5 mm × 0.5 mm and a thickness of 400 nm were deposited by sputtering on the surface of each PZT. Figure 6 shows the leakage current characteristics of a PZT compact film with a porosity of approximately 35% impregnated with silicone oil, the change in leakage current characteristics of a PZT dense coagulated film with a porosity of 11% to 15% before and after impregnation with silicone oil, and the leakage current characteristics of a PZT dense coagulated film with a porosity of approximately 10% or less impregnated with silicone oil. In a normal green compact with a porosity of approximately 35%, even when impregnated with silicone oil, the extremely high leakage current quickly led to dielectric breakdown. In contrast, in a PZT dense cohesive film with a porosity of 11% to 15%, the leakage current was reduced by about four orders of magnitude, and by impregnating this with silicone oil, a further reduction in leakage current of about one order of magnitude was confirmed. Furthermore, in a PZT dense cohesive film with a porosity of approximately 10% or less impregnated with silicone oil, the leakage current was reduced by 4.67 x 10 even with a high applied electric field of 500 kV / cm. -7 A / cm 2 It showed very good insulation properties.
[0033] Figure 7 shows the polarization characteristics of a PZT highly dense cohesive film with a porosity of 10% or less impregnated with silicone oil, and a PZT highly dense cohesive film with a porosity of approximately 10% impregnated with a solution of TiO2 nanoparticles dispersed in ethanol and pressed again at 900 MPa. Both of them show saturated polarization characteristics. In addition, the remanent polarization value (P r ) is 38μC / cm 2 , coercive electric field (E c ) was 280 kV / cm, while for the dense PZT aggregates impregnated with a solution of TiO2 nanoparticles dispersed in ethanol, P r is 37 μC / cm 2 , coercive electric field (E c ) increased to 400 kV / cm. This suggests that the functionality of the PZT dense coagulated film can be controlled by impregnating it with nanoparticles or resin.
[0034] Example 3: Stacking of dense aggregates sandwiched between electrode layers (Fig. 8) (1) Manufacturing of Unit 1 The first particles, PZT particles (average particle size : 1550 nm) was attached. The first PZT particles were synthesized by the molten salt method using PZT-LQ powder manufactured by Sakai Chemical Industry Co., Ltd. The first PZT particles were weighed with a micro-analytical balance (SHIMADZU, MODEL: AEM-5200) and transferred to a 50cc glass container containing ethanol, and dispersed for 1 minute with ultrasonic waves of 350W and 20kHz using an ultrasonic homogenizer (SONIC & MATERIALS, MODEL: VCX750). The solution was transferred to an airbrush coating system (GSI Creos, PS311 airbrush set) and spray-painted onto the SUS304 of a transfer plate prepared in advance on a hot plate set at 60℃, thereby attaching the first PZT particles to the SUS304 surface.
[0035] The second particles were attached onto the first particles so that the mixing ratio of the second particles (volume occupied by the second particles / total volume of the first particles and the second particles) was between 15% and 30%. The second particles were sprayed in the same manner as the first particles. The second particles consisted of PZT particles (average particle size The second PZT particles were obtained by first preparing a sintered body using Sakai Chemical Industry's PZT-LQ powder, powdering it in a mortar, placing it in a zirconia ball mill pot together with zirconia balls and acetone, pulverizing it in a planetary ball mill, drying the acetone, dispersing the resulting powder in ethanol, centrifuging it, and classifying it. The second PZT particles were also dispersed in ethanol in the same way as the first PZT particles, and then sprayed onto the surface of the SUS304 to which the PZT particles were attached, causing them to adhere onto the first PZT particles.
[0036] The SUS304 with the first and second particles attached was removed from the hot plate and several disks with a diameter of 13 mm were cut out. A 13 mm diameter aluminum foil (film thickness 20 μm) substrate with an aluminum terminal 1 mm wide and 5 mm long was sandwiched between the first and second PZT particles attached to the SUS304, and solidification pressure was applied to solidify the PZT particles on both sides of the aluminum foil substrate, transferring the first and second particles to both sides of the substrate. The substrate is preferably a metal or carbon having an elastic modulus of 180 GPa or less. The consolidation pressure is lower than the pressure at which the raw material fine particles are crushed, and it is preferable that the consolidation pressure is 2 GPa or less. In this experiment, the first and second particles were transferred eight times to both sides of an aluminum foil at 450 MPa, and then the foil was pressed at 900 MPa using hard chrome-plated steel, depositing an insulating PZT layer on the aluminum foil to a thickness of 20 μm on each side. An electrically conductive dense aggregate film may be provided between the substrate and the insulating dense aggregate film of PZT.
[0037] As a comparative reference example, we used an electrically conductive mesh foil as the substrate and attempted to transfer the first and second PZT particles. The electrically conductive mesh foil was fabricated by sputtering gold electrodes on both sides of a PET sheet on which holes with a diameter of 250 μm were drilled at a pitch of 300 μm by laser processing. A microscope photograph of the obtained coagulated film is shown in Figure 9. As shown in Figure 9, the first and second PZT particles could not be transferred sufficiently to the holes in the substrate and their surroundings (dark areas scattered in 14), and the first and second PZT particles could not be solidified. Note that 13 is an area where part of the coagulated film formed by transfer has been wiped off, as an indication that areas where the coagulated film is not formed will be dark areas.
[0038] Next, 1 cm of PZT was applied to the surface of the dense agglomerated film on both sides. 2 An electrode layer was deposited by sputtering gold of φ. Since the next step involves impregnating the dense PZT agglomerate film with PMMA, the deposition of this electrode layer is preferably carried out by a deposition method that does not block the pores of the dense agglomerate. A sputtering method or a vacuum deposition method may be used, and a method that forms a dense agglomerate film having electrical conductivity may also be used.
[0039] Both sides of a dense PZT film with gold electrodes sputtered on it were impregnated with PMMA dissolved in PEGMEA, and an electrically conductive 1cm2 film with terminals 1mm wide and 5mm long was fabricated. 2 Sandwiched between mesh foil of φ, 6N / cm 2While restraining the sample with , PEGMEA was evaporated at 60 °C, and PMMA was solidified. In this experiment, the electrically conductive mesh foil was created by sputtering gold electrodes on both sides of PET that had been laser-machined to create holes with a diameter of 250 μm and a pitch of 300 μm; however, metal foil with similarly fine holes is also suitable, as is cloth woven with electrically conductive threads such as metal or carbon, or electrically conductive mesh foil produced with a 3D printer. The relative dielectric constant of the thus obtained unit 1 was 136.
[0040] As a comparative example, an electrically conductive mesh foil without an electrode layer was directly bonded to the highly dense aggregated films on both sides of the substrate in the same manner as above using PMMA dissolved in PEGMEA. The dielectric constant of the resulting unit was 0.67. From this, it is considered that the electrically conductive mesh foil alone did not provide sufficient adhesion to the highly dense PZT coagulated film as an electrode.
[0041] As a comparative example, we attempted to bond an electrically conductive mesh foil directly to a highly dense PZT coagulated film without using PMMA dissolved in PEGMEA and applying a solidification pressure of 1 GPa; however, as shown in Figure 10, bonding was not possible (the left and right sides of Figure 10 show mesh foil, and the center shows a substrate with highly dense coagulated films on both sides).
[0042] (2) Manufacturing of Unit 2 Three of the unit 1 elements manufactured in (1) above were stacked (unit 2). PMMA dissolved in PEGMEA was impregnated between each unit 1, and a pressure of 6 N / cm was applied. 2 The PMMA was solidified by volatilizing the PEGMEA at 60°C while restraining the sample with . This made it possible to produce an integrated electric element unit that did not require constant holding down with a restraining jig when stacking the units 1.
[0043] <Example 4> Removal of resin solidified on the surface of a highly dense flocculated membrane It is very difficult to impregnate a press-molded dense coagulation membrane with the right amount of resin, solidify it, and expose only the surface of the dense coagulation membrane. For example, if a liquid containing a resin such as PMMA dissolved in a solvent is impregnated and then the solvent is evaporated to solidify, the solidified resin may not reach the surface of the dense coagulation membrane due to the reduction in volume caused by the evaporation of the solvent, or there may be too much liquid applied and the excess resin may solidify to form a surface layer. In addition, when epoxy resin or the like is impregnated, if you try to scrape off the excess resin that has overflowed onto the surface before solidifying with silicone rubber or the like, the dense coagulation membrane that has only been press-molded may easily be destroyed.
[0044] For example, if an upper electrode is formed by sputtering or the like on a ferroelectric dense cohesive film with a surface layer formed by solidifying excess resin, an electric field is concentrated in the solidified excess resin between the upper electrode and the ferroelectric dense cohesive film, resulting in a problem that the ferroelectricity and piezoelectricity are not exhibited. Also, if an upper electrode is deposited in advance on the dense cohesive film and then impregnated with resin, and the excess resin is solidified to form a surface layer, there is a problem that the solidified excess resin in the surface layer inhibits the connection between the upper electrode and the circuit.
[0045] The inventors discovered that the rate at which the resin that has impregnated and solidified inside the highly dense coagulated film and the resin that has solidified on the surface and formed the surface layer dissolve in an organic solvent and the rate at which they swell when immersed in an organic solvent are different, and discovered that the manufacturing method can solve the above-mentioned problems. Next, a specific manufacturing method will be described using PZT as an example.
[0046] The first particles, PZT particles (average particle size : 1550 nm) was attached. The first PZT particles were synthesized by the molten salt method using PZT-LQ powder manufactured by Sakai Chemical Industry Co., Ltd. The first PZT particles were weighed with a micro-analytical balance (SHIMADZU, MODEL: AEM-5200) and transferred to a 50cc glass container containing ethanol, and dispersed for 1 minute with ultrasonic waves of 350W and 20kHz using an ultrasonic homogenizer (SONIC & MATERIALS, MODEL: VCX750). The solution was transferred to an airbrush coating system (GSI Creos, PS311 airbrush set) and spray-painted onto a SUS304 transfer plate prepared in advance on a hot plate set at 60℃, thereby attaching the first PZT particles to the SUS304 surface.
[0047] Next, the second particles were attached onto the first particles so that the mixing ratio of the second particles (volume occupied by the second particles / combined volume of the first particles and the second particles) was between 15% and 30%. The second particles are sprayed in the same manner as the first particles. The second particles are PZT particles (average particle size The second PZT particles were obtained by first preparing a sintered body using Sakai Chemical Industry's PZT-LQ powder, powdering it in a mortar, placing it in a zirconia ball mill pot together with zirconia balls and acetone, pulverizing it in a planetary ball mill, drying the acetone, dispersing the resulting powder in ethanol, centrifuging it, and classifying it. The second PZT particles were also dispersed in ethanol in the same way as the first PZT, and then sprayed onto the surface of the SUS304 to which the PZT particles were attached, causing them to adhere onto the first PZT particles.
[0048] The SUS304 with the first and second particles attached was removed from the hot plate and 2 A number of disks of φ were cut out, and the first and second particles were pressed against an aluminum foil (film thickness 20 μm) substrate, pressed, transferred, and solidified onto the substrate. The substrate is preferably a metal or carbon with an elastic modulus of 180 GPa or less. The solidification pressure is preferably lower than the pressure at which the raw material fine particles are crushed, and is preferably 2 GPa or less. In this experiment, the pressure was 1000 MPa. The first and second particles were pressed and transferred from the SUS304 to the aluminum foil substrate nine times, resulting in a highly dense cohesive film of PZT laminated on the aluminum foil. Figure 11 (a) is a schematic diagram of a sample in which an Au upper electrode was sputtered onto the surface of this highly dense cohesive film of PZT. The area of the Au upper electrode was 0.5 mm × 0.5 mm, and the thickness was 400 nm.
[0049] Next, as shown in (b) of Figure 11, the surface was impregnated with epoxy resin. A low-viscosity epoxy resin, 50-minute curing, two-part type (manufactured by Shin-Nihon Resin Co., Ltd.) was used. After this impregnation process, the epoxy resin was crosslinked and solidified by heat treatment at 70°C for 2 hours or more.
[0050] Next, as shown in Figure 11(c), several mL of cyclohexane was applied to the surface of the sample and left to stand for 30 minutes to swell only the excess epoxy resin on the surface. Then, as shown in Figure 11(d), it was carefully peeled off with tweezers to expose the highly dense PZT agglomerated film and the Au upper electrode as shown in Figure 11(e).
[0051] Figure 12(a) is an SEM image of the surface of the Au upper electrode shown in Figure 11(e). As a comparative reference example, Figure 12(b) shows an SEM image of the surface before peeling off the excess epoxy resin shown in Figure 11(b). In the comparative reference example, the PZT particles cannot be confirmed by SEM due to the excess epoxy resin on the surface, but it can be confirmed that the PZT highly dense agglomerated film impregnated with epoxy resin and the Au upper electrode have been exposed by the swelling treatment with cyclohexane and peeling described above.
[0052] The solidified excess epoxy resin on the surface comes into contact with cyclohexane at a "face" level, but when cyclohexane reaches the epoxy resin impregnated in the highly dense PZT cohesive film, it comes into contact at a "point", making it less likely to swell, and as a result, it is thought that it is possible to remove only the excess epoxy resin on the surface.
[0053] Figure 13(a) shows the polarization characteristics of a highly dense cohesive PZT film impregnated with epoxy resin. A fully saturated hysteresis loop can be confirmed. In the comparative reference example shown in Figure 13(b), where excess epoxy resin was left on the surface, the excess epoxy resin hindered the circuit connection between the Au upper electrode and the ferroelectricity evaluation device, and no hysteresis loop could be observed.
[0054] In addition, when Kapton adhesive tape was attached to the surface of the PZT dense cohesive film impregnated with epoxy resin, which showed this saturated hysteresis loop, and then peeled off, the PZT dense cohesive film did not peel off from the aluminum foil substrate, but the PZT dense cohesive film impregnated with silicone oil was easily peeled off from the aluminum foil substrate. This enabled the production of a highly dense cohesive film with high bonding strength and ceramic functionality.
[0055] <Example 5> Fabrication of a flexible sheet-shaped all-solid-state lithium-ion battery All-solid-state lithium-ion batteries using polymer solid electrolytes have the problem that they have lower ionic conductivity than liquid electrolytes, and cannot be charged or discharged unless the temperature is 50°C or higher. In addition, polymer electrolytes have the problem that they are highly viscous and take a long time to be impregnated, and there are also problems with increasing the energy density by densely containing active materials. The highly dense aggregates according to the present invention have the characteristic of being impregnated with liquid all over, and it has been found that by using this structure in the electrode layer to impregnate the polymer solid electrolyte, the diffusion distance of lithium ions can be significantly shortened, and an all-solid-state lithium-ion battery that can operate even at room temperature can be produced.
[0056] The all-solid-state lithium-ion battery preferably comprises a positive electrode sheet having a highly dense coagulated film of a positive electrode active material formed on a substrate, and a negative electrode sheet having a coagulated film of a negative electrode active material formed on a substrate, and preferably has a feature that the positive electrode sheet and the negative electrode sheet are impregnated with a polymer electrolyte. The polymer electrolyte may be a non-crosslinked polymer electrolyte, but is preferably a crosslinked and solidified polymer solid electrolyte. In addition, it is preferable to have a polymer electrolyte layer between the highly dense coagulated film of the positive electrode active material and the coagulated film of the negative electrode active material.
[0057] The thickness of the dense agglomerate of the positive electrode sheet and the thickness of the agglomerate film of the negative electrode sheet are each preferably about 3 μm to 50 μm, and may be between 1 μm and 300 μm. The porosity of the dense agglomerate of the positive electrode sheet is preferably 20% or less, and the porosity of the agglomerate of the negative electrode sheet is preferably 35% or less. Positive electrode active materials include, but are not limited to, lithium cobalt oxide (LCO), lithium manganese oxide, lithium nickel oxide, nickel cobalt manganese oxide, nickel cobalt aluminum oxide, lithium iron phosphate, and the like. The negative electrode active material may include, but is not limited to, lithium titanate (LTO), carbon, metal silicon, and the like. The substrate of the positive electrode sheet is preferably aluminum, but is preferably a metal coated with corrosion-resistant Au or Pt with an elastic modulus of 180 GPa or less, or carbon. The thickness of the substrate of the positive electrode sheet is preferably between 10 μm and 30 μm, but may be between 5 μm and 50 μm. The substrate of the negative electrode sheet is preferably aluminum coated with Au to a thickness of 10 nm to 1 μm, but Li + The negative electrode sheet may be coated with Cu or Pt, which is resistant to the above-mentioned stress, or may be coated with a metal having an elastic modulus of 180 GPa or less, or may be carbon. The thickness of the substrate of the negative electrode sheet is preferably between 10 μm and 30 μm, but may be between 5 μm and 50 μm. The polymer electrolyte layer may be a non-crosslinked polymer electrolyte, but is preferably a crosslinked and solidified polymer solid electrolyte. The higher the ion conductivity of the polymer electrolyte layer, the better. -6The thickness of the polymer electrolyte layer is preferably 1 μm to 20 μm, but may be between 100 nm and 50 μm. Next, a specific example of the manufacturing method will be described.
[0058] LiCoO2 (LCO) powder was used as the positive electrode active material. This powder is commercially available (Cellseed 5hV, manufactured by Nippon Chemical Industry Co., Ltd.). 0.5g of LCO, 50mL of ethanol, and silicon nitride balls (10mmφ, 5mmφ, and 2mmφ, totaling approximately 500g) were placed in a 500cc zirconia container (manufactured by Fritsch) and ground for 12 hours at 200 rpm using a planetary ball mill (manufactured by Fritsch, P-6 Classic Line).
[0059] Ethanol was added so that the liquid removed from the planetary ball mill became 250 mL, and the mixture was centrifuged for 5 minutes at a centrifugal force of 470 × g. The SEM image of the precipitated particles is shown in Figure 14 (a). The average particle size was about 1 μm. These particles were used as the first LCO particles. The solution remaining after centrifugation was evaporated in a vacuum dryer until it became about 70 mL. The resulting liquid was used as the second LCO solution, and the particles obtained by drying the second LCO solution were used as the second LCO particles. The SEM image of the second LCO particles is shown in Figure 14 (b). It can be seen that the second LCO particles are more thoroughly pulverized than the first LCO particles. When the second LCO particles were observed by SEM at a higher magnification, it was confirmed that they contained nanosheets with a thickness of several nm and an area ranging from several nm to about 1 μm, as shown in Figure 14 (c).
[0060] Next, an alumina-coated SUS304 was prepared by depositing an alumina film of about 1 μm thickness on a stainless steel SUS304 foil (film thickness 20 μm) by the AD method. LCO particles, which will be the first particles, were attached to the alumina film surface. The first LCO particles were weighed with a micro-analytical balance (SHIMADZU, MODEL: AEM-5200) and transferred to a 50 cc glass container containing ultra-dehydrated heptane, and dispersed for 1 minute with ultrasonic waves of 150 W and 20 kHz using an ultrasonic homogenizer (SONIC & MATERIALS, MODEL: VCX750). The solution was transferred to an airbrush coating system (GSI Creos, PS311 airbrush set) and spray-painted onto the alumina-coated SUS304 of a transfer plate prepared in advance on a hot plate set at 70°C, thereby attaching the first LCO particles to the alumina-coated SUS304 surface.
[0061] Next, the second LCO particles were attached on the first LCO particles so that the mixing ratio of the second LCO particles (volume occupied by the second particles / volume of the first and second particles combined) was between 15% and 35%. The second LCO particles were spray-painted using a second LCO solution. As with the first LCO particles, the second LCO particles were attached on top of the first LCO particles by spraying it on the surface of the alumina-coated SUS304 to which the first LCO particles had been attached.
[0062] The alumina-coated SUS304 with the first and second LCO particles attached was removed from the hot plate and subjected to a heat treatment at 350°C for 5 minutes in air with a dew point temperature of -40°C or lower.
[0063] Next, a rectangular aluminum foil substrate (area 6 mm × 10 mm, film thickness 12 μm) was prepared. In order to easily visually identify it as a positive electrode sheet, an Au film was sputtered to a thickness of 400 nm on the surface of this rectangular aluminum foil opposite to the surface on which the LCO was solidified. In air with a dew point temperature of -40°C or lower, the first and second LCO particles were pressed against the aluminum surface, pressed and transferred, and solidified on the substrate. The solidification pressure is preferably lower than the pressure at which the raw material fine particles are crushed, and has the characteristic of being 2 GPa or less. In this experiment, the pressure was 420 MPa. The first and second particles were pressed and transferred from the alumina-coated SUS304 to the aluminum foil substrate four times, thereby laminating a dense coagulated film of LCO on the aluminum foil. The thickness of the dense coagulated film of LCO was about 5 μm. A positive electrode sheet was obtained by these methods.
[0064] Li4Ti5O as negative electrode active material 12 The powder used was a commercially available powder (LTO-2, manufactured by Xiamen Tmax Battery Equipments Limited) in which the surface of LTO particles was coated with carbon, and a powder synthesized from reagents.
[0065] First, 1 g of commercially available carbon-coated LTO particles was dispersed in 250 mL of ethanol to prepare a solution, which was then centrifuged at a centrifugal force of 75×g, the liquid was removed, and the solution was thoroughly dried to obtain a powder. These powder particles were designated the first LTO particles. Figure 15(a) shows an SEM image of these particles. The average particle size was approximately 800 nm.
[0066] Next, Li4Ti5O 12Lithium carbonate (Kojundo Chemical, LIH06XB) and titanium oxide (Kojundo Chemical, TIO14PB) were weighed out so that the stoichiometric composition was 20 g, and placed in a 500 cc zirconia container (Fritsch) together with 200 mL of ethanol and silicon nitride balls (10 mmφ, 5 mmφ, 2 mmφ, evenly distributed, totaling approximately 500 g), and ground and mixed for 2 hours at 500 rpm using a planetary ball mill (Fritsch, P-6 Classic Line). The resulting liquid was transferred to a tray and thoroughly dried at 80°C, after which the resulting mixed powder was transferred to an alumina crucible and heat-treated at 800°C for 6 hours. The obtained powder was again placed in a 500 cc zirconia container (manufactured by Fritsch) together with 200 mL of ethanol and silicon nitride balls (10 mmφ, 5 mmφ, and 2 mmφ, approximately 500 g in total, evenly spaced), and ground at 500 rpm for 2 hours using a planetary ball mill (manufactured by Fritsch, P-6 Classic Line). The powder was then transferred to a tray and thoroughly dried at 80°C, after which it was transferred to an alumina crucible and heat-treated at 800°C for 6 hours to obtain LTO powder.
[0067] 1 g of this LTO powder, 50 mL of ethanol, and silicon nitride balls (10 mmφ, 5 mmφ, and 2 mmφ evenly distributed, totaling approximately 500 g) were placed in a 500 cc zirconia container (manufactured by Fritsch) and ground for 18 hours at 250 rpm using a planetary ball mill (manufactured by Fritsch, P-6 Classic Line). Ethanol was added so that the resulting liquid was 500 mL, and then centrifuged for 15 minutes at a centrifugal force of 836 × g, and the ethanol was evaporated in a vacuum dryer until the centrifuged liquid was 100 mL. This concentrated liquid was used as the second LTO solution. Half of this second LTO solution (50 mL) was transferred to a separate container and further dried thoroughly in a vacuum dryer to obtain LTO powder. The particles of this LTO powder were used as the second LTO particles. The SEM image of the second LTO particles is shown in Figure 15 (b). It can be confirmed that the second LTO particles are more thoroughly ground than the first LTO particles. When this second LTO particle was observed under a higher magnification with an SEM, it was confirmed that it contained nanosheets with a thickness of several nm and an area ranging from several nm to approximately 1 μm, as shown in Figure 15 (c).
[0068] Next, an alumina-coated SUS304 was prepared by depositing an alumina film of about 1 μm thickness on a stainless steel SUS304 foil (film thickness 20 μm) by the AD method. LTO particles, which will be the first particles, were attached to the alumina film surface. The first LTO particles were weighed with a micro-analytical balance (SHIMADZU, MODEL: AEM-5200) and transferred to a 50 cc glass container containing ethanol, and dispersed for 1 minute with ultrasonic waves of 150 W and 20 kHz using an ultrasonic homogenizer (SONIC & MATERIALS, MODEL: VCX750). The solution was transferred to an airbrush painting system (GSI Creos, PS311 airbrush set) and spray-painted onto the alumina-coated SUS304 of a transfer plate prepared in advance on a hot plate set at 70 °C, thereby attaching the first LTO particles to the surface of the alumina-coated SUS304.
[0069] Next, the second LTO particles and the first LTO particles were weighed with a micro-analytical balance (SHIMADZU, MODEL: AEM-5200) so that the mixing ratio of the second LTO particles (volume occupied by the second particles / volume of the first and second particles combined) was about 25%, and transferred to a 50 cc glass container containing ethanol, and a solution was prepared by dispersing the particles for 1 minute with ultrasonic waves of 150 W and 20 kHz using an ultrasonic homogenizer (SONIC & MATERIALS, MODEL: VCX750). The solution containing the first and second LTO particles was sprayed on the surface of the alumina-coated SUS304 to which the first LTO particles were attached, in the same manner as the first LTO particles, to attach the mixture of the first and second LTO particles onto the first LTO particles.
[0070] Next, the second LTO particles were applied on top of the first and second mixed LTO particles so that the mixture ratio of the first LTO particles and the second LTO particles applied by spraying initially was between 15% and 35%. The second LTO solution was used for spray coating the second LTO particles.
[0071] The alumina-coated SUS304 with the first and second LTO particles attached was removed from the hot plate and subjected to a heat treatment at 350°C for 5 minutes in an atmosphere with a dew point temperature of -75°C or less and an oxygen concentration of 50 ppm or less.
[0072] A square aluminum foil (area 8mm x 12mm, film thickness 13μm) substrate was prepared with Au sputtered on its surface to a thickness of about 400nm. The first and second LTO particles were pressed against the Au sputtered surface in air with a dew point temperature of -40℃ or lower, and pressed and transferred onto the substrate. This Au sputtered film was composed of aluminum and Li + This is a barrier layer to prevent the reaction of Li + Materials with high resistance to this, such as Cu or Pt, may also be used. The solidification pressure should preferably be lower than the pressure at which the raw material fine particles are crushed, and be 2 GPa or less. In this experiment, a pressure of 420 MPa was applied. The first and second particles were pressed and transferred from the alumina-coated SUS304 to the aluminum foil substrate, and this process was repeated four times to laminate an LTO agglomerated film on the aluminum foil. The thickness of the LTO agglomerated film was approximately 5 μm. Using these methods, a negative electrode sheet was obtained.
[0073] This section explains a method for constructing an all-solid-state lithium-ion battery by impregnating a positive electrode sheet and a negative electrode sheet with a polymer solid electrolyte and bonding the positive electrode sheet and negative electrode sheet using the polymer solid electrolyte. For the polymer solid electrolyte, a commercially available product made by Osaka Soda Co., Ltd., "Product name: All-solid polymer electrolyte" (polymer electrolyte dissolved at 20 wt% in acetonitrile and crosslinking initiator) was used. The ionic conductivity of the all-solid polymer electrolyte synthesized in this experiment was 2×10 -5 It was S / cm.
[0074] (a) in Figure 16 shows the negative electrode sheet. The polymer electrolyte and crosslinking initiator dissolved in acetonitrile were thoroughly mixed in the specified amounts in air with a dew point temperature of -40°C or less, and the solution was impregnated into the negative electrode sheet as shown in (b) in Figure 16. The acetonitrile was then thoroughly volatilized to prepare a negative electrode sheet impregnated with the polymer electrolyte and crosslinking initiator as shown in (c) in Figure 16. The positive electrode sheet was similarly impregnated, and the acetonitrile was thoroughly volatilized to prepare a positive electrode sheet impregnated with the polymer electrolyte and crosslinking initiator. These two sheets of positive and negative electrodes were laminated together as shown in (d) in Figure 16 so that no air could enter, and were heat-treated at 70°C for 1 hour at a dew point temperature of -70°C or less and an oxygen concentration of 50 ppm or less, to crosslink the polymer electrolyte, and an all-solid-state lithium-ion battery was produced as shown in (e) in Figure 16. The thickness of the polymer electrolyte layer provided between the positive and negative electrode sheets was approximately 20 μm.
[0075] As a comparative reference example, a commercially available all-solid-state polymer electrolyte sheet with a thickness of 50 μm (ionic conductivity: 5×10 -5 They also fabricated an all-solid-state lithium-ion battery with a 1.2 S / cm between the positive and negative electrode sheets.
[0076] The charge / discharge curve of the fabricated all-solid-state lithium-ion battery is shown in Figure 17. The evaluation conditions were 25°C and 0.01C. The all-solid-state lithium-ion battery in which the highly dense coagulated film was impregnated with the polymer solid electrolyte exhibited characteristics reflecting the typical charge / discharge curve of LCO, and it was confirmed that charging and discharging could be performed at room temperature. On the other hand, the battery fabricated by sandwiching the all-solid-state polymer electrolyte sheet was not able to charge and discharge sufficiently.
[0077] As a result, by impregnating every corner of the highly dense coagulated membrane with the polymer solid electrolyte, it was possible to create an oxide-based all-solid-state lithium-ion battery that can operate even at room temperature.
[0078] <Example 6> Flexible and foldable all-solid-state lithium-ion battery Conventional lithium-ion batteries, whether liquid or solid-state, have achieved high capacity by rolling up a battery sheet and placing it in a case, as in "rectangular lithium-ion batteries," or by stacking battery sheets and connecting the terminals from the edges, as in "laminated lithium-ion batteries." However, there are issues with this, such as restrictions on the case shape and the fact that the positive and negative terminals are taken out from the edges, which imposes restrictions on the overall shape of the battery.
[0079] The inventors found that a battery sheet that is flexible and can be folded can be produced by using a highly dense agglomerated membrane as an electrode layer, impregnating this structure with a polymer solid electrolyte, and further embedding ceramic particles in the polymer electrolyte layer. It is believed that this battery sheet can be used to produce batteries with a high degree of freedom in shape, such as the folded battery shape shown in FIG. 18(a) and the battery shape shown in FIG. 18(b) in which the edges of the battery sheet are folded and stacked. Furthermore, with these folded and stacked battery structures, both the positive and negative terminals can be taken out directly from not only the edges but also the faces. In addition, a solid-state battery in which the folded battery sheet is stacked with a cloth containing resin such as CFRP or FRP and the entire structure is covered with cross-linked resin can be used as a structural member for, for example, a smartphone case.
[0080] This flexible and foldable battery sheet preferably includes a polymer solid electrolyte layer having ceramic particles embedded therein between the above-mentioned positive electrode sheet and negative electrode sheet impregnated with a polymer solid electrolyte, as shown in (a) of FIG. + Materials that do not react with the negative electrode active material, such as SiC, SiO2, Si3N4, and oxides such as alumina and zirconia, may also be used. In addition, lithium ion conductors with a lower reduction potential than the negative electrode active material, such as garnet-type lithium ion conductor Li7La3Zr2O 12 Ceramic particles are also acceptable. particle sizeis preferably between 100 nm and 10 μm. The thickness of the polymer solid electrolyte layer in which the ceramic particles are embedded is preferably about 1 μm to 10 μm, and may be between 100 nm and 50 μm. The content of the ceramic particles in the polymer solid electrolyte layer is preferably between 10% and 70% in the case of an oxide that does not exhibit lithium ion conductivity, and may be between 10% and 80% in the case of a lithium ion conductor, and may be a highly dense aggregate. Next, an example of a specific method for manufacturing a foldable and flexible all-solid-state lithium ion battery will be described.
[0081] Alumina particles (Sumitomo Chemical, Sumicorundum AA-2, average thickness 20 μm) were applied to the surface of stainless steel SUS304 (film thickness 20 μm). particle size :2μm) was attached. The AA-2 particles were weighed using a micro-analytical balance (SHIMADZU, MODEL: AEM-5200) and transferred to a 50cc glass container containing ethanol. The particles were then dispersed for 1 minute using an ultrasonic homogenizer (SONIC & MATERIALS, MODEL: VCX750) at 150W and 20kHz. The solution was then transferred to an airbrush coating system (GSI Creos, PS311 airbrush set) and spray-painted onto a SUS304 transfer plate that had been prepared in advance on a hot plate set to 60°C, thereby adhering the AA-2 particles to the SUS304 surface.
[0082] The SUS304 with AA-2 attached was removed from the hot plate and heat-treated at 350°C for 5 minutes in an environment with a dew point temperature of -40°C or less, after which the AA-2 particles were pressed against the positive and negative electrode sheets for pressure transfer. The positive and negative electrode sheets were prepared in the same manner as in Example 5. The pressure for pressure transfer is preferably lower than the pressure at which the raw material fine particles are crushed, and is preferably 2GPa or less. In this experiment, pressure was applied at 420MPa. The AA-2 particles were pressed and transferred from the SUS304 to the positive and negative electrode sheets once.
[0083] Next, the positive electrode sheet and the negative electrode sheet to which AA-2 was attached were each impregnated with 20 wt% all-solid polymer electrolyte manufactured by Osaka Soda Co., Ltd., as in Example 5, and the acetonitrile was sufficiently evaporated. Then, the high density coagulated film of the positive electrode and the coagulated film of the negative electrode were bonded together so as not to allow air to enter, and then a pressure of 7 kN was applied to push out the excess polymer electrolyte before crosslinking to produce a battery sheet. The thickness of the polymer electrolyte layer was about 5 μm, which was thinner than that of Example 5.
[0084] When the battery sheet having a polymer electrolyte layer not containing ceramic particles as in Example 5 was subjected to a press treatment to extrude excess polymer electrolyte, the highly dense agglomerated film of the positive electrode active material came into contact with the agglomerated film of the negative electrode, causing a short circuit.
[0085] The end of the obtained battery sheet was folded 180°, and then heat treatment was performed at 70°C for 1 hour at a dew point temperature of -70°C or less and an oxygen concentration of 50 ppm or less to crosslink the polymer electrolyte and make it fully solid. Figure 19 (b) and (c) show photographs of the folded all-solid-state lithium-ion battery sheet. Figure 19 (d) shows a photograph of the folded all-solid-state lithium-ion battery sheet after charging, stacking it as shown in Figure 18 (b), connecting it to an LED, and confirming that it lit up.
[0086] FIG. 20 shows the charge / discharge characteristics of the folded all-solid-state lithium-ion battery sheet. The evaluation was performed at 0.01C and 25°C. The characteristics reflected the charge / discharge curve specific to LCO. As a comparative reference example, the battery of Example 5 was folded in the same manner, and then the polymer solid electrolyte was crosslinked to make it all-solid, but the positive and negative electrodes were short-circuited and charging was not possible. Furthermore, even when the battery of Example 5 was folded, the positive and negative electrodes were short-circuited and charging was not possible.
[0087] For reference, FIG. 21 shows a comparison of impedance characteristics before and after folding a 9 μm thick polymer solid electrolyte between 13 μm thick aluminum foils. Although it is sufficiently thinner than the polymer electrolyte layer of Example 5, no change was observed before and after folding, and no short circuit occurred. The cause of the short circuit caused by folding the battery of Example 5 is thought to be that folding the battery caused the ceramic particles of the high density agglomerated film of the positive electrode or the agglomerated film of the negative electrode to flow, applying a strong shear force to the polymer solid electrolyte, and the polymer solid electrolyte was cut. Therefore, it is thought that the ceramic particles provided in the polymer electrolyte layer have the effect of suppressing the flow of the positive and negative electrode active materials that act when the battery is folded. This enabled the creation of a flexible, folded-shaped all-solid-state lithium-ion battery. [Explanation of symbols]
[0088] 1: 1st particle 2: 1st cavity 3:Second particle 4:Second cavity 5: Voids at grain boundary triple junctions 6: Sintered particles 7: Unit 1 8: Unit 2 9: Base material 10: Highly dense agglomerated film 11: Electrode layer 12: Electrically conductive mesh foil 13: The area where the first and second PZT particles remaining on the electrically conductive mesh foil have been removed with a cloth 14: The first and second PZT particles remaining on the electrically conductive mesh foil (bright scattered areas) 15: Au sputtered upper electrode 16: PZT ceramic particles 17: Aluminum base material 18: Crosslinked epoxy resin 19: Epoxy resin swollen with cyclohexane 20: Negative electrode active material 21: Substrate of negative electrode sheet 22: Polymer electrolyte before crosslinking and crosslinking initiator dissolved in a solvent 23: Polymer electrolyte before crosslinking after evaporating the solvent and crosslinking initiator 24: Base material of positive electrode sheet 25: Positive electrode active material 26: Crosslinked and solidified polymer electrolyte 27: Electrical conductor 28: Ceramic particles
Claims
1. The following steps (1) to (4): (1) a step of depositing first ceramic particles on a transfer plate to form a first ceramic particle layer; (2) forming a second ceramic particle layer by depositing second ceramic particles having a particle size smaller than that of the first ceramic particles on the first ceramic particle layer; (3) disposing a substrate on the second ceramic particle layer and applying a first pressure to the substrate from above the substrate, thereby embedding the second ceramic particles in gaps between the first ceramic particles and bringing at least some of the second ceramic particles into contact with the substrate; and (4) Step of removing the transfer plate and forming a ceramic particle laminate on the substrate by performing the transfer step including the steps of:
2. comprising treating the ceramic particle stack with a liquid to cause the liquid to impregnate the ceramic particle stack; The ceramic particle laminate has a porosity of 20 volume % or less, The method according to claim 1 , wherein the ratio of the volume of voids communicating with the outer surface to the total volume of voids in the ceramic particle laminate is 65% or more.
3. The method according to claim 1 , wherein the transfer plate is a stainless steel substrate or an alumina-coated stainless steel substrate.
4. The method according to claim 1 , wherein the elastic modulus of the substrate is 180 GPa or less.
5. The method according to claim 1 , wherein the substrate is made of aluminum or carbon.
6. The method of claim 1 , wherein the first pressure is less than or equal to 2 GPa.
7. The method of claim 1 , wherein the second ceramic particles have an average particle size of 1 μm or less.
8. The ceramic particle laminate has a porosity of 20 volume % or less, 2. The method according to claim 1, wherein the ratio of the volume of the voids connected to the outer surface to the total volume of the voids in the ceramic particle laminate is 65% or less.
9. The method of claim 1 further comprising forming an electrode on the ceramic particle stack.
10. The method of claim 2 , wherein the liquid is a solution of a polymer.
11. The method of claim 1, further comprising forming an electrode on the ceramic particle stack. The method of claim 10 further comprising selectively removing the polymer on the electrodes.
12. The method according to claim 11 , wherein the removal is performed by dropping an organic solvent to swell the polymer on the electrode, and peeling off the swollen polymer.
13. The method of claim 10 , wherein the polymer is a polymer electrolyte.
14. 2. The method of claim 1, wherein the first ceramic particles and the second ceramic particles are each selected from PZT, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, nickel cobalt manganese oxide, nickel cobalt aluminum oxide, lithium iron phosphate, and lithium titanate particles.
15. The method of claim 1, wherein the positioning of the substrate is performed without sintering the first ceramic particle layer and the second ceramic particle layer.
16. The method of claim 1, wherein in the ceramic particle laminate, the volume of the second ceramic particles relative to the total volume of the first ceramic particles and the second ceramic particles is 15% to 30%.
Citation Information
Patent Citations
Method of producing particulate arrangement structure, and method of producing optical medium
JP2004261746A
Brittle material structure and method for forming the same
JP2006043993A
Method for arranging nanocrystal, method for preparing nanocrystal film, substrate covered with nanocrystal film and method for producing the same
JP2012188335A
High dielectric nanosheet laminate, high dielectric element, and method for manufacturing high dielectric thin film element
JP2012240884A
Ceramic positive electrode-solid electrolyte assembly
JP2014096350A